Experiential Marketing as a Basis for Modern Communications with Consumers - Sergeevna, Budovich Lidia (International Review of Management and Marketing, 2018)
Amid saturated markets and growing competition when consumer needs can be satisfied in many ways, not many products (services) have unique qualities demanded by the target segment, which would help them stand out against the background of numerous alternative products of competitors. Companies find a way out by applying the experiential marketing that focuses on consumers’ desire to entertain, fulfil their whims and enjoy. The term ‘experiential marketing’ (see below the origin of the term and the characteristic of the approach) is derived from the word ‘empiricism’ taken from the Greek word ‘empeiria’ [á¼Î¼Ï€ÎµÎ¹ÏÎ¯Î±] meaning ‘experience’) according to which a sensual experience is a source of knowledge and all knowledge is based on experience. Its foundation is underpinned by the following strategic experiential modules (SEMs): Sense, Feel, Think, Act and Relate that are highlighted in accordance with M. Ponty’s Modular Theory of Mind and that represent different types of consumer experiences. Thus, the Feel SEM is a consumer’s emotionally coloured state that occurs as a response to the impact of marketing tools both before and after a purchase, and that manifests itself in the formation of the consumer’s emotional attitude to the advertised product or to the company as a whole. Let us discuss each SEM in detail. Keywords: Experiential Marketing, Communications, Consumers JEL Classifications: M3, Ðœ31, M37 https://doi.org/10.32479/irmm.6909